FACTORS AFFECTING FINANCIAL DISTRESS IN THE CONSUMER INDUSTRY SECTOR DURING THE COVID-19 PANDEMIC - Tumbelaka, Kathy Paulina; Imelda, Elsa; Simina, Juni (International Journal of Application on Economics and Business, 2024)
The COVID-19 pandemic has led to changes in financial performance and a decline in global economic conditions. This study aims to obtain empirical evidence about the influence of Corporate Social Responsibility (CSR), firm size, and firm age on corporate financial distress in the cyclical and non-cyclical consumer sectors during the COVID-19 pandemic. The research design used in this study is descriptive research with quantitative methods. The research sample was selected using purposive sampling, which contains 80 companies as sample. Hypothesis testing is done using a regression analysis model of panel data. The data processing for this study using some application such as Microsoft Excel and EViews 10. The results revealed that Corporate Social Responsibility has no influence on financial distress, the size of a company has a significant positive influence over financial distresses, and the age of the company has significant negative influence upon financial distress. This means that both the size and age of the company are interrelated indicators that should be considered because they can affect the risk of financial distress.